Proposed model to employ computer-mail in physical education classes for schools Educational Karkh / 1 medium - Mohameed, Abdulsalam (Journal of Physical Education, 2011)
This study aimed at reconstructing the Technology Approach with respect to psychology families, proposing a practical model to implement education and e-learning systems, defining the needs of planning curricula based on knowledge economy use, and recommendations of how to utilize e-learning systems in schools. The study tried to answer four questions:1)What is the new concept of technology approach in designing curriculum?, 2) what is the practical model needed to implement computerized education system according to educational technology?, 3) what are the needs of planning curricula based on knowledge economy use?, 4) What are the recommendations of utilizing e-learning systems in schools